Investigation SSR marker from Camellia sinensis growing in Thai Nguyen province - Yen, Hoang Thi Thu; Nhung, Duong Thi; Thanh Hoan, Ha Thi; Viet, Le Bac; Hoang, Nguyen Huy (Academia Journal of Biology, 2016)
SSR molecular markers are commonly applicated in breeding, mapping of useful genes, genetic mapping, researching population and linkage genetics. In this study, we analyzed the characteristics of the size of some SSR fragments and evaluated genomic diversity of 18 tea varieties/clones collected from Tan Cuong commune, Song Cau tea Company and Minh Lap commune (Dong Hy district), Thai Nguyen province. Amplification results of SSR fragments with 14 specific primer pairs from research samples are indicated sequence diversity and diversity of the DNA fragments to be amplified. Using NTSYS version 2.1 software to analysis diversity of DNA fragments amplified by PCR-SSR, research varieties/lines tea is divided into two main groups with coefficient of variation between them with the remaining 0.4. Additionally, nucleotide sequences of SSR markers which related gene encoding glyoxalase and sucrose 6-phosphatephosphatase are sequenced and analyzed as a basis for teas breeding. Investigation result indicated repeat motif diferrent when compare research tea samples and submitted sequence. Citation: Hoang Thi Thu Yen, Duong Thi Nhung, Ha Thi Thanh Hoan, Le Bac Viet, Nguyen Huy Hoang, 2017. Investigation SSR marker from Camellia sinensis growing in Thai Nguyen province. Tap chi Sinh hoc, 39(1): 68-79. DOI: 10.15625/0866-7160/v39n1.7594 *Corresponding author: yenhtt@tnus.edu.vn. Received 30 December 2015, accepted 20 March 2017